The Gospel according to St Matthew - Pasolini, Pier Paolo, 1922-1975; Bini, Alfredo; Colli, Tonino Delli; Irazoqui, Enrique; Salerno, Enrico Maria; Tartan Video (United Kingdom : Tartan Video, 1999)
A life of Christ from the Annunciation to the Resurrection based on the text Pasolini regarded as the most socially critical of the Gospels. Pasolini's Christ is a revolutionary, born among the poor and preaching the gospel of the poor, in a spirit emphatically that of the recently deceased Pope John XX111. The film includes allusions to mediaeval and renaissance painting and music from Bach to negro gospel.
Original Gospel text from: Pro Civitate Christiana-Assisi.
Italian dialogue, English subtitles.
Original Italian title: Il vangelo secondo Matteo.
Original motion picture produced by Alfredo Bini for L' Arco Film and Lux Cie Cinematografique de France, 1964.
Director, script, Pier Paolo Pasolini ; producer, Alfredo Bini; photography, Tonino Delli Colli ; editor, Nino Baragli.
Enrique Irazoqui.
Keywords: Bible films; Feature films -- Italy